Simulating responses of riparian ecosystem network complexity to flow regime shifts in arid regions - Mengmeng Zhang; Chengyi Zhao; Jianting Zhu; Wangya Han; Wenqi Jiang (Ecological Indicators)
Human activities have significantly altered flow regimes, but the effects of shifting flow regimes on riparian species interactions and the ecosystem network remain unclear. This study applied a modified community-wide population model, integrated with network theory, to simulate the responses of the riparian ecosystem to potential future flow regimes in a desert oasis in northwestern China. Results indicate that the riparian ecosystem network in the desert oasis is inherently unstable under the Heihe River’s current hydrological conditions, characterized by considerable intra-annual and inter-annual runoff variability, as even minor changes in flow regimes could alter the network. Specifically, increased frequency of drought year simplifies the network, while heightened flood year frequencies (not exceeding 85%) create a more intricate network. Additionally, longer flood duration (more extended overlap with seed dispersal periods) significantly improves network connectivity and redundancy. Notably, the keystone status of species within the flow regime influences the network structure. With reduced flooding and more homogeneous flow, the keystone roles shift from trees and shrubs to herbs. This underscores the essential role of flooding events in sustaining riparian ecological networks. Thus, flood frequency, timing, and duration, alongside water quantity, should be considered in ecological restoration efforts for desert oasis environments. The study’s methodology and findings provide a scientific foundation for developing comprehensive management guidelines to regulate riparian areas under global change.